Recursos didácticos interactivos - Chango Masaquiza, Willian Vinicio (2017)
Nowadays education has new ways of teaching and learning. Therefore, it has been necessary to incorporate new interactive teaching resources in order to innovate the teaching process in students. Thus, it is intended to be critical and reflective students for this reason it has been necessary to increase new innovative resources to motivate students and avoid the use traditional materials; then, the interactive resources updated in all subjects should be used, but especially in the subject of mathematics. The principal purpose of this research study was to determine the importance of the use of interactive teaching resources in order to promote meaningful learning among students. The lack of use of interactive teaching resources by teachers was evidenced and it affects the students’ academic performance, that is why it was inquired about the implementation of teaching resources, it is intended to improve academic quality within the teaching-learning process, each teacher must comply with the work in a more appropriate form and it means that interactive teaching resources should be used....